Acute transverse myelitis in COVID-19 infection. Issue 8 (11th August 2020) - Chow, Chian Chiang Nicholas; Magnussen, John; Ip, Jerome; Su, Yuen
Abstract : A 60-year-old man presented to hospital with bilateral lower limb weakness, urinary retention and constipation. He had been diagnosed with COVID-19 10 days prior. Clinical examination revealed global weakness, increased tone, hyperreflexia and patchy paresthesia in his lower limbs bilaterally. Preliminary blood tests performed revealed a mildly elevated C reactive protein and erythrocyte sedimentation rate but was otherwise unremarkable. MRI scan of his whole spine demonstrated hyperintense T2 signal centrally from T7 to T10, suggestive of acute transverse myelitis. A lumbar puncture showed elevated protein count but normal glucose and white blood cell count. Serological testing for other viruses was negative. His neurological symptoms improved significantly after treatment with intravenous methylprednisone. This case highlights a potential neurological complication of COVID-19 infection.